FORMATION OF PROJECT MANAGERS’ COMPETENCIES IN THE IT SPHERE UNDER THE CONDITIONS OF THE RISKS AND UNCERTAINTY - BARSKYI, Borys; ORIEKHOV, Mykhaylo (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article defines the peculiarities of the formation of project managers’ competencies in the IT sphere in conditions of risk and uncertainty in comparison with generally accepted world standards in this field. On the basis of a generalization of the generally accepted standards for the competencies of project managers in the world and their comparison with the requirements put forward by employers in the Ukrainian market for candidates for this vacancy, it was concluded that there are features of the latter that reflect both modern changes in the labor market and the realities of work in under the conditions of the challenges of the war, namely, it was determined that in the description of the requirements of employers on the Ukrainian labor market, 23% of the internationally accepted ICB Standard is covered by a medium and high level of attention to the competencies of candidates for the position of project manager. At the same time, 93% of employers demand that candidates possess a foreign (English) language at an above-average level, which can be explained by the high level of internationalization of the Ukrainian IT services sector. In addition, 82% of the jobs surveyed included additional interdisciplinary requirements for basic knowledge of such digital tools.The modern peculiarities of the conditions of activity on the Ukrainian market in the conditions of war were reflected in such additional personal qualities and professional competences as the ability to organize a business process based on Agile principles, the ability to work in multitasking mode, flexibility, stress resistance, anti-fragility as the ability to function in conditions of uncertainty and get motivation for self-improvement from mistakes.
Keywords: management; project management; IT sphere; risks; lack of recognition; competences; digital competences; interdisciplinary